Muscle Coenzyme Q^sub 10^ Level in Statin-Related Myopathy - Lamperti, Costanza; Naini, Ali B; Lucchini, Valeria; Prelle, Alessandro (Archives of neurology (Chicago), 2005)
Statin drugs (3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors) reduce the level of cholesterol by inhibiting the synthesis of mevalonate, an intermediary in the cholesterol biosynthetic pathway. Use of statin drugs has been associated with a variety of skeletal muscle-related complaints. Coenzyme Q^sub 10^ (CoQ^sub 10^), a component of the mitochondrial respiratory chain, is also synthesized from mevalonate, and decreased muscle CoQ^sub 10^ concentration may have a role in the pathogenesis of statin drug-related myopathy. To measure the CoQ^sub 10^ concentration and respiratory chain enzyme activities in muscle biopsy specimens from 18 patients with statin drug-related myopathy and to look for evidence of apoptosis using the TUNEL (terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick-end labeling) assay. An open-labeled study of CoQ^sub 10^ concentration in muscle from patients with increased serum creatine kinase concentrations while receiving standard statin drug therapy. Neuromuscular centers at 2 academic tertiary care hospitals. Muscle structure was essentially normal in 14 patients and showed evidence of mitochondrial dysfunction and nonspecific myopathic changes in 2 patients each. Muscle CoQ^sub 10^ concentration was not statistically different between patients and control subjects, but it was more than 2 SDs below the normal mean in 3 patients and more than 1 SD below normal in 7 patients. There was no TUNEL positivity in any patients. These data suggest that statin drug-related myopathy is associated with a mild decrease in muscle CoQ^sub 10^ concentration, which does not cause histochemical or biochemical evidence of mitochondrial myopathy or morphologic evidence of apoptosis in most patients.